Didactic Physics potential in the development of critical thinking - Соломенко, Артем Олександрович; Коновал, Олександр Андрійович; Туркот, Тетяна Іванівна (Pedagogy of Higher and Secondary Education, 2017)
The article is devoted to the development of critical thinking in the subjects of educational activity. The basic elements that make up the base of critical thinking were allocated. In the article there was reviewed and analyzed the composition of the school course «Physics». The features of the course of physics were identified. It was found that the consideration of the challenging tasks is followed by the successful formation and development of critical thinking. The importance of the use of questions to develop critical thinking has been proved. The relationship between modern scientific picture of the world and the development of critical thinking of those who study physics was adduced in the article. The subjects of critical thinking are different products of culture and science, which provide different information. There was shown the importance of the values of emotional and rational components of critical thinking. The use of physical science for the development of critical thinking has been proved. Physics develops students because it provides various activities – observations, investigations and experiments, the study of phenomena and laws, principles of actions of different devices. We believe that the development of critical thinking as independent thinking, is more effective while using the productive teaching methods and setting problem tasks. During the development of critical thinking at the physics lessons the development of students’ abilities is possible, such as: the ability to analyze information logically; to raise new issues; to make independent decisions; make reasonable estimates; apply the results to standard and non-standard situations; the ability to take a position on the discussed issues and justify it; to listen to the opponent, consider the arguments carefully and analyze their logic. Of course, this article does not cover the entire range of problems associated with critical thinking, with the capabilities of critical thinking for a better understanding of physics and vice versa – using physics as a subject for developing critical thinking. We have wanted to show that physics has the didactic potential for successful formation and development of critical thinking. Further scientific research will be directly related with the teaching systems, and creating teaching technologies.